“Onde a ação se une com a ideia": as batalhas de Rap em São Carlos-SP - Lima, Engel Rodrigues de (2022)
In this research, I analyze sociologically the Battles of Rap and the Slams in São Carlos- SP city, with the objective of identify the social representation, narratives, tensions, contradiction and possible linguistic and symbolic negotiation that are constructed and communicated in the environment of the events. The research is based on dialogues with 5 interlocutors- Stevan, Arlequina, Curinga, Peninha e THC das Ruas- that, through the experience reports, signify and give meaning to the cultural occupation of public spaces in the city. In addition to the interview (or talk) the analysis is also based on photographs, videos, reports and music letters related to the field of research. It is worth pointing out that cultural practices of Battles of Rap and Slams are characterized in a special way by disputes, especially in verses, and are consecrated by their respective particularities in producing culture in the contemporary. That said, I search specifically: a) identify how the Battle of Raps, that occured in the São Carlos-SP city, are constructed as popular youth culture, above all on the periphery and, at the same time, as a counterculture; b) understand the construction of cultural identity in these movements, take into account their gender, sexuality, race and class cleavages; c) analyze how the public space, specially the city squares, are understood and negotiated through the structures of feeling of these movements. From a theoretical point of view, I especially use the contributions of Cultural and Post- Colonial Studies. In general lines, the research demonstrates, through the experience reports of these subjects, the plurality of cultural forms that emerge in the Diaspora, able of articulate the creative agency of individuals and movements that speak of struggle, resistance, emancipation and, at the same time, disputes strategic positions in the cultural hegemony of the city. In this sense, this movement (re)places the agency bringing the past and writing another reading of the past in the present, pointing to a future that is not programmatic or metatheoretical, but concerned with solving everyday battles. Therefore, the research, by placing the experience and black creative agency at the center of the analysis, reveals with power, the ways of thinking about black cultures, cultural identity and belonging in the Diaspora.